REGIONAL SECURITY AND COOPERATION ISSUES IN U.S. POLICY TOWARD POST-SOVIET CENTRAL ASIA - MAKHMUDOV, Aziz (CENTRAL ASIA AND THE CAUCASUS, 2012)
It stands to reason that at the early stage of independence, the five republics in the Central Asian region—Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan—previously closely linked to the Soviet economic and political systems, faced a number of challenges, most of which were inherited from the Czarist-Soviet regimes. Coping with the challenges posed by the transition period required foreign support, and all the republics, except Turkmenistan, have been engaged in active cooperation with global powers such as the U.S.Considering the main features of the Western powers’ involvement in the post-Soviet arena, we can agree with Gertrude Schroeder, who defined the first years since 1991 as a period of “mutual learning.” On the one hand, the leaders of the newly independent states have learned from their experience of establishing a market economy at the speed and with the specifics permitted by domestic reality. On the other hand, international organizations and countries have obviously contributed enormously to this learning process and, through investment and bilateral assistance programs, also learned much about dealing with a previously unknown environment. Schroeder refers to this process as follows: